EDUCAÇÃO INFANTIL COMO DIREITO FUNDAMENTAL DA CRIANÇA CEGA CONGÊNITA - Rocha, Railda Lopes da (2014)
This dissertation refers to an exploratory research aimed at Early Childhood Education as a fundamental right of congenitally blind children from birth to five years, or children who have gone blind in the first year of life. It intends to comprehend the benefits of integration in childrens educational public spaces, the federal public policies, and the ones from the city of São Paulo, as well as the relation of the right to education in Special Education. To do so, it explores the nature of blindness, linking historical aspects of education of visually impaired people and public policies related to the right to education. Although Education has aroused interest in many society corporations and UN agencies, involving legal documents as the Universal Declaration of Human Rights (1948), the Brazilian Federal Constitution (1988), the Statute of the Child and Adolescent (1990), the UNESCO Salamanca Statement (1994) which is a watershed in the Special Education , the National Education Guidelines and Framework Law (1996) which guarantees education as a right for all, according to the constitutional statement and even though the Early Childhood Education is essential as a foundation of basic education, it is not seen as a fundamental right yet. This research shows that both congenitally blind children and their parents face obstacles when seeking schools: lack of availability in the childcare and EMEIs (kindergartens), teachers with insufficient education to work with the inclusion of students with special educational needs, stigma, and absence of physical structure for students accessibility and autonomy. Lack of classrooms to support inclusion and equipment of childhood education, as well as specialized staff, are some of the examples of the situation at hand, which needs an intervention in the city of São Paulo, with the accountability of responsible authorities, for violating a right that is fundamental according to national and international laws.